Fabricating nanostructures on fused silica using femtosecond infrared pulses combined with sub-nanojoule ultraviolet pulses - Yu, Xiaoming; Chang, Zenghu; Corkum, P. B.; Lei, Shuting (My University, 2014)
Circular craters with diameters of 500 nm are fabricated on the surface of fused silica by femtosecond ultraviolet–infrared (UV–IR) pulse trains with 0.8 nJ UV pulse energy. UV damage thresholds at different IR energies and UV–IR delays are measured. Diameters and depths of the ablated craters can be modified by adding the IR pulse and varying the UV–IR delays. These results demonstrate the feasibility of nanomachining using short wavelength lasers with pulse energy far below normal damage thresholds.
Keywords: Femtosecond phenomena; Nonlinear optics at surfaces; Ultraviolet